The Output Characteristics of the Photovoltaic Array for Laser Wireless Power Transmission Within Non-Kolmogorov Turbulence considering Pointing Error - Zhenyang Xiong; Xing Du; Guoning Xu; Hao Du; Zhongzhen Jia; Sheng Wang; Rong Cai; Guixuan Ding (IEEE Photonics Journal)
This paper examines the output characteristics of the photovoltaic (PV) array in a laser wireless power transmission (LWPT) system considering atmospheric turbulence and pointing error r (r, θ). Firstly, we propose a theoretical model for studying the laser energy of each PV cell in non-Kolmogorov turbulence by introducing power in bucket (PIB). Then, to obtain the output characteristics of the PV array, we build the equivalent model based on the carrier continuity equation and bipolar transport equation. The results demonstrate that the power at the maximum power point (MPP) Pmpp and the system efficiency η2 descend 50.9% and 51.5%, in the cases of r (20 mm, 45°) compared with r (0, 0), respectively, when the transmission distance is 1000 m. The variation range (5.1 V to 22.3 V) of the voltage at MPP Vmpp with r (10 mm, 45°) is distinctly larger than that (21.9 V to 23.2 V) with r (0, 0) when the transmission distance varies from 0 m to 2000 m. The findings of this study are valuable for the design of DC-DC converter, maximum power point tracking (MPPT) algorithm and the closed loop control circuit in LWPT system to make it efficient and stable operation.